Trace element composition and genesis mechanism of the Fuli Pb-Zn deposit in Yunnan: LA-ICP-MS and in situ S-Pb isotopic constraints - Liang, Xingyu; Li, Bo; Zhang, Xinyue; Qin, Huaikun; Li, Gao; Zhang, Chengnan (Frontiers in Earth Science, 2023)
The Fuli Pb-Zn deposit in Yunnan is located in the southeast of the Sichuan-Yunnan-Guizhou (SYG) Pb-Zn metallogenic province in South China. Lead and zinc reserves total approximately 0.3 million tons with an average grade of 18.68% Pb+Zn. The stratiform ore occurs in the interlayer fracture zone of the middle Permian Yangxin formation dolomite. The main sulfides of the Fuli Pb-Zn deposit consist of sphalerite, galena, and pyrite, while dolomite and calcite are the main gangue minerals. Mineralization exhibits massive, disseminated, vein and breccia textures. Sphalerites of two colors (black and red) have been identified in the Fuli deposit. LA-ICP-MS analysis revealed that the black and red sphalerites were enriched in Cd, Cu, Ga, and Ge and depleted in Fe, Mn, and In to varying degrees. The aforementioned elements exhibit homogeneous patterns in the LA-ICPMS time resolution profiles, which is consistent with variations in the concentrations of major elements like Zn and S. This indicates that these elements may occur in sphalerite as a result of isomorphous substitution. However, elements such as As, Sb, Pb, and Ag fluctuate greatly in the LA-ICPMS time resolution profiles, suggesting that these elements may exist as fine inclusions. Thus, the different colors of the Fuli sphalerite may be attributed to various elements such as Ni, Cu, and Ga; Ni and Cu result in purple Sp, Cu renders sphalerite red, and Ga imparts a yellow color. The sulfur isotope compositions of the two sphalerites exhibit little variation, with δ34S values ranging from 15.57‰ to 16.91‰, indicating the enrichment of 34S. These results are consistent with the sulfur isotopic compositions of Permian marine sulfates, indicating that thermochemical sulfate reduction was the main source of the reduced sulfur in the hydrothermal fluids. In situ Pb isotopic composition analysis revealed 208Pb/204Pb, 207Pb/204Pb, and 206Pb/204Pb values for galena in the range of 38.5–38.651, 15.666–15.733, and 18.539–19.124, respectively. The in situ Pb isotopic ratios of most galenas plot on the field of the basement metamorphic rocks of the Kunyang Group. These in situ Pb isotopic signatures reveal that the metallogenic metals are mainly derived from crustal basement. The findings of this study suggest that the Fuli Pb-Zn deposit is a MVT Pb-Zn deposit controlled by the interlayer compressional structure with characteristics of carbonate-hosted, epigenetic, simple mineral symbiosis, high Pb-Zn grade, and abundant Cd, Ga, and Ge along with other dispersed elements.